Emulsion Separation Rate Enhancement via Microwave Heating Technology - A.N, Alia Anisa; Nour, A. H. (2009)
The role of microwave concept in demulsifying water-in-crude oil emulsion was assessed experimentally for heating rate, volume rate of heat generation and dielectric properties. In this study, a microwave demulsification method was utilised for emulsions; 20-80 % and 50-50 % w/o emulsion, water and crude oil with varied microwave exposure time. The prepared emulsion was vigorously shaken with three blade propeller at 1500 rpm in 5 minutes. Results have shown for both phase ratios, the rate of temperature increased as decreasing the dielectric properties and volume heat of generation. Higher water content in the emulsion absorbed more microwave radiation thus, friction of molecules are more rapid and converted into heat and performed the higher dielectric properties.